Empirical Analysis of Cultural Memory Awakening in Youth Groups through Digital Recreation of Auspicious Pattern Cultural Products - Xiao, Shanpeng; Mat Yaakob, Nur Haizal; Mohamad, Sharih Ahmad (Digital Technologies Research and Applications, 2026)
This study examines that digitally regenerated auspicious pattern designs may suggest meaningful influence on cultural memory awakening among young urban populations. Moreover, the significant findings could indicate that environmental psychology and social psychology provide the key theoretical foundation for a four-dimensional progressive framework: digital design perception → emotional resonance → cultural memory awakening → cultural behavioral intention. Furthermore, the evidence may suggest that a total of 387 participants aged 18 to 35 were recruited from urban settings to support the results. In light of the data, three complementary methods—questionnaire surveys, eye-tracking experiments, and in-depth interviews—could demonstrate that the study examined three digital regeneration formats: static graphic reconstruction, dynamic interactive display, and AR scene embedding. Study shows perceptual characteristics, memory awakening mechanisms, behavioral outcomes assessed across formats. However, the significant results may suggest that AR scene embedding received the highest overall perceptual preference ratings across the study. Notwithstanding individual variation, the data could suggest that the social interaction context exerted a significant positive moderating influence on memory awakening. Evidence shows individual differences in cultural capital affect awakening depth. Therefore, the significant findings may suggest that cultural memory awakening could demonstrate notable positive effects on purchase intention, dissemination intention, and intergenerational transmission intention. Moreover, the findings could suggest that these results may provide significant practical guidance for leveraging digital cultural creative design in the inheritance of traditional culture. Thus, the important evidence may indicate that the study appears to offer a systematic theoretical basis for future research.